Leukemic progenitor cells are susceptible to targeting by stimulated cytotoxic T cells against immunogenic leukemia‐associated antigens. Issue 9 (13th May 2015) - Schneider, Vanessa; Zhang, Lu; Rojewski, Markus; Fekete, Natalie; Schrezenmeier, Hubert; Erle, Alexander; Bullinger, Lars; Hofmann, Susanne; Götz, Marlies; Döhner, Konstanze; Ihme, Susann; Döhner, Hartmut; et al.
<x xml:space="preserve">Abstract</x> Leukemic stem cells (LSC) might be the source for leukemic disease self‐renewal and account for disease relapse after treatment, which makes them a critical target for further therapeutic options. We investigated the role of cytotoxic T‐lymphocytes (CTL) counteracting and recognizing LSC. Leukemia‐associated antigens (LAA) represent immunogenic structures to target LSC. We enriched the LSC‐containing fraction of 20 AML patients and hematopoietic stem cells (HSC) of healthy volunteers. Using microarray analysis and qRT‐PCR we detected high expression of several LAA in AML cells but also in LSC. PRAME (p = 0.0085), RHAMM (p = 0.03), WT1 (p = 0.04) and Proteinase 3 (p = 0.04) showed significant differential expression in LSC compared with HSC. PRAME, RHAMM and WT1 are furthermore also lower expressed on leukemic bulk. In contrast, Proteinase 3 indicates a higher expression on leukemic bulk than on LSC. In colony forming unit (CFU) immunoassays, T cells stimulated against various LAA indicated a significant inhibition of CFUs in AML patient samples. The LAA PRAME, RHAMM and WT1 showed highest immunogenic responses with a range up to 58‐83%. In a proof of principle xenotransplant mouse model, PRAME‐stimulated CTL targeted AML stem cells, reflected by a delayed engraftment of leukemia (p = 0.0159). Taken together, we demonstrated the expression of several LAA in LSC. LAA‐specific T cells are able to hamper LSC in immunoassays and in a mouse model, which suggests that immunotherapeutic approaches have the potential to target malignant stem cells.